1981
DOI: 10.1007/bf01870982
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate transport in rabbit ileum: Characterization of the serosal border anion exchange process

Abstract: The preceding paper [30] shows that transepithelial ileal SO4 transport involves Na-dependent uptake across the ileal brush border, and Cl-dependent efflux across the serosal border. The present study examines more closely the serosal efflux process. Transepithelial mucosa (m)-to-serosa (s) and sto-m fluxes (Jms, Jsm) across rabbit ileal mucosa were determined under short-circuit conditions. SO4 was present at 0,22 mM. In standard C1, HCO3 Ringer's, jso4 was 81.3 +5.3 (1SE) and jso4 was 2.5_+0.2 nmol cm-2hr-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…In recent studies of the rat proximal and distal colon, however, 2 mM mucosal DIDS and 1 mM 4-acetamido-4'-isothiocyanatostilbene-2,2'-disulfonic acid did not alter J", Jcn,' or Isc despite other evidence suggesting that anion exchange was present (18, 28). Similar observations have been made in rabbit ileum (29) and rabbit colon (30). Our results therefore do not absolutely exclude the participation of Cl/HCO3 ion exchange in the rat distal colon's response to CO2.…”
Section: Discussionsupporting
confidence: 70%
“…In recent studies of the rat proximal and distal colon, however, 2 mM mucosal DIDS and 1 mM 4-acetamido-4'-isothiocyanatostilbene-2,2'-disulfonic acid did not alter J", Jcn,' or Isc despite other evidence suggesting that anion exchange was present (18, 28). Similar observations have been made in rabbit ileum (29) and rabbit colon (30). Our results therefore do not absolutely exclude the participation of Cl/HCO3 ion exchange in the rat distal colon's response to CO2.…”
Section: Discussionsupporting
confidence: 70%
“…After accumulation within the cell, sulfate may exit at the luminal face of the cell in exchange for bicarbonate or another anion (4). The luminal anion exchanger is similar to exchangers described in other tissues except that its affinity for chloride apparently is much lower (5)(6)(7)(8)(9)(10).…”
supporting
confidence: 66%
“…SITS, a widely used inhibitor of anion exchange in other systems, abolished the bicarbonate stimulation of sulfate uptake. Phloretin, which also inhibits anion exchange in several systems (10), was an effective (=70%) inhibitor. Thiosulfate, presumably a competitor for the sulfate site (13,18,19), also virtually eliminated the HCOj stimulation of sulfate uptake at 15 sec.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In various other types of cells, a saturable anion transport can be found that can also be inhibited by stilbene disulfonates. For example, in Ehrlich ascites tumor cells (2 I) and rabbit ileum (19), sulfate transport can be strongly inhibited by these compounds, whereas chloride transport is almost unaffected. Active chloride transport in the amphibian cornea is inhibited on both the aqueous and tear side of the cells by DIDS (2).…”
mentioning
confidence: 99%